Microscopic images of IODP Hole 389-M0104A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Microscopic images (photomicrographs) of selected samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) taken during the Onshore phase of this expedition (2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen). For visual inspection and imaging an Olympus SZX-7 stereo microscope (WHSZ 10x observation tube) equipped with an Olympus DP-22 digital camera has been used. File naming follows the standard IODP file naming convention starting with the section identifier followed by the sample interval, the image running number and the magnification factor, each separated from each other and the section identifier by underscore. For example, 389-M0102C-03R-1_14-15cm_image_3_8x.JPG is the image number three from 14-15 cm within section one of core three (rotary type) from hole M0102C, using eightfold enlargement. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025